Seasonal occurrence, predation and parasitism of Leucoptera coffeella (Guérin-Méneville, 1842) (Lepidoptera: Lyonetiidae) in coffee Plants cssociated with grevilla trees - Souza, Tiago Pinho; Castellani, Maria Aparecida; Lemos, Raimunda Nonata Santos de; Maluf, Raquel Pérez; Moreira, Aldenise Alves; Silva, Bruna Santos; Ribeiro, Edenilson Batista (Coffee Science - ISSN 1984-3909, 2014)
The leaf miner, Leucoptera coffeella, is a key pest in coffee crops, causing significant losses. This work aimed to study the seasonal occurrence of leaf miner and the infestation rates of parasitism and predation natural pest in coffee associated with grevillea trees in Southwestern Bahia, Brazil. The experiment consisted of five fields (treatments) and four replicates, totaling 20 plots. Treatments were defined by the spacing of grevillea associated with Catuaí (IAC 144): Treatment 1 – shaded - without grevillea; Treatment 2 - 18x18m = 31 grevilleas.ha-1; Treatment 3 - 12x12m = 69 grevilleas.ha-1; Treatment 4 - 6.0 x12m = 139 grevilleas.ha-1 and Treatment 5 - 6.0 x6,0m = 277 grevilleas.ha-1. The plots consisted of four (T4 and T5) and six coffee plants (T1, T2 and T3) around one grevillea plant. We quantified the number of leaves with mines, mines per leaf, total mines, mine predated and parasitized from September/2011 to June/2012. The results indicated that the influence of the increased density of grevillea trees the population of the leaf miner is not uniform over time, presenting unfavorable the period September to December 2011, to densities in the band 180-220 grevilleas.ha-1, from which promotes the growth of the insect population. In the period from February to June 2012, the increase in the density of grevillea trees acts negatively on the pest population. The predation has the same trend as the leaf miner infestation in relation to the density of grevillea trees, while the parasitism does not show a pattern of behavior with respect to that variable. The relation between predation and parasitism is positive.